2016
DOI: 10.1634/theoncologist.2015-0503
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Methadone as a Second-Line Opioid for Cancer Pain in an Outpatient Clinic: A Prospective Open-Label Study

Abstract: Introduction. Most clinical reports on methadone rotation describe outcomes in hospitalized patients. The few studies that have included outpatients are retrospective. The aim of this study was to assess the efficacy and safety of methadone as a second‐line opioid in adult patients with advanced cancer after rotation in routine clinical practice at a palliative care outpatient clinic. Patients and Methods. This was a prospective, open‐label study of 145 patients whose treatment was rotated from other opioids t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
11
0
5
Order By: Relevance
“…32 Recently, a prospective study of 145 patients with advanced cancer who were treated in an outpatient palliative care clinic with rotation to methadone found a significant improvement in pain relief without an increase in opioid toxicity. 33 In 2013, a federally convened expert panel developed a consensus statement regarding methadone induction and stabilization. The comprehensive report offered specific recommendations for initiating methadone treatment and concluded that methadone can be safely prescribed provided the risks are recognized, there is adequate patient education, and there is a plan of intervention at signs of toxicity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32 Recently, a prospective study of 145 patients with advanced cancer who were treated in an outpatient palliative care clinic with rotation to methadone found a significant improvement in pain relief without an increase in opioid toxicity. 33 In 2013, a federally convened expert panel developed a consensus statement regarding methadone induction and stabilization. The comprehensive report offered specific recommendations for initiating methadone treatment and concluded that methadone can be safely prescribed provided the risks are recognized, there is adequate patient education, and there is a plan of intervention at signs of toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…A prior retrospective analysis has shown that the outpatient administration of methadone in patients with cancer is considered safe and has a side effect profile similar to that of other opioids . Recently, a prospective study of 145 patients with advanced cancer who were treated in an outpatient palliative care clinic with rotation to methadone found a significant improvement in pain relief without an increase in opioid toxicity . In 2013, a federally convened expert panel developed a consensus statement regarding methadone induction and stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…A simple analgesic agent is often ineffective, and multimodal pharmacotherapy, including opioids, non-opioid analgesics, and adjuvant drugs (antiepileptics, antidepressants, and muscle relaxants), is required, although its effectiveness has been shown to be limited (2,3). Recent studies have shown that rotation switching of opioids to methadone was effective for refractory neuropathic pain (6,20). Other studies reported the efficacy of intervention strategies, including epidural analgesia (9,19), injection from a psoas sheath catheter (21) or intrathecal catheter (19,22), and dorsal rhizotomy (23).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Because of incomplete cross‐tolerance between different types of opioids, rotation is effective in reducing MEDD while improving analgesia and maintaining tolerance to severe side effects such as respiratory depression. Rotation to a specific opioid also indicated for the pharmacological treatment of dependence (methadone or buprenorphine) may provide additional risk reduction. Opioid rotation is successful in about two thirds of patients with cancer, resulting in a decreased MEDD, accompanied by improved pain, depression, overall well‐being , and survival .…”
Section: Management Strategiesmentioning
confidence: 99%